2023
DOI: 10.3389/frph.2023.1105390
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions to reduce child marriage and teen pregnancy in sub-Saharan Africa: A systematic review of quantitative evidence

Abstract: IntroductionChild marriage and teen pregnancy have negative health, social and development consequences. Highest rates of child marriage occur in sub-Saharan Africa (SSA) and 40% of women in Western and Central Africa got married before the age of 18. This systematic review was aimed to fill a gap in evidence of effectiveness to reduce teen pregnancy and child marriage in SSA.MethodsWe considered studies conducted in sub-Saharan Africa that reported on the effect of interventions on child marriage and teen pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…Feyissa, G y col. (Feyissa et al, 2023) muestran que el matrimonio infantil, definido como matrimonio antes de los 18 años, se asocia con un mayor riesgo de embarazo adolescente, lo que a su vez plantea graves riesgos para la salud de los adolescentes. De acuerdo con la UNICEF (UNICEF, 2018) Las investigaciones enfatizan la importancia de las intervenciones para abordar estos problemas de manera efectiva, especialmente en regiones como el África subsahariana y el sur de Asia, donde prevalecen el matrimonio infantil y el embarazo adolescente.…”
Section: Discussionunclassified
“…Feyissa, G y col. (Feyissa et al, 2023) muestran que el matrimonio infantil, definido como matrimonio antes de los 18 años, se asocia con un mayor riesgo de embarazo adolescente, lo que a su vez plantea graves riesgos para la salud de los adolescentes. De acuerdo con la UNICEF (UNICEF, 2018) Las investigaciones enfatizan la importancia de las intervenciones para abordar estos problemas de manera efectiva, especialmente en regiones como el África subsahariana y el sur de Asia, donde prevalecen el matrimonio infantil y el embarazo adolescente.…”
Section: Discussionunclassified
“…Child marriage, de ned as marriage before the age of 18 years, has been associated with an increased risk of adolescent pregnancy [15,17]. Moreover, child marriage eliminates the sexual and reproductive health rights of adolescents and limits their opportunities to achieve their full potential.…”
Section: Introductionmentioning
confidence: 99%
“…However, educational and contraceptive-promoting interventions should also include parents, teachers and society leaders for a strong linkage between adolescents and family planning providers. A systematic review of quantitative studies on the effectiveness of interventions aimed at reducing child marriage and teenage pregnancies found that programs on adolescent empowerment through life skills building as well as wealth and health skills building were effective at reducing unintended pregnancies(39). However, some of the interventions have cost implications which may affect their sustainability in resource limited settings.…”
mentioning
confidence: 99%